Identification of potential genetic components involved in the deviant quorum-sensing signaling pathways of Burkholderia glumae through a functional genomics approach - Chen, Ruoxi; Barphagha, Inderjit K.; Ham, Jong Hyun (Frontiers in Cellular and Infection Microbiology, 2015)
Burkholderia glumae is the chief causal agent for bacterial panicle blight of rice. The acyl-homoserine lactone (AHL)-mediated quorum-sensing (QS) system dependent on a pair of luxI and luxR homologs, tofI and tofR, is the primary cell-to-cell signaling mechanism determining the virulence of this bacterium. Production of toxoflavin, a major virulence factor of B. glumae, is known to be dependent on the tofI/tofR QS system. In our previous study, however, it was observed that B. glumae mutants defective in tofI or tofR produced toxoflavin if they grew on the surface of a solid medium, suggesting that alternative signaling pathways independent of tofI or tofR are activated in that growth condition for the production of toxoflavin. In this study, potential genetic components involved in the tofI- and tofR-independent signaling pathways for toxoflavin production were sought through screening random mini-Tn5 mutants of B. glumae to better understand the intercellular signaling pathways of this pathogen. Fifteen and three genes were initially identified as the potential genetic elements of the tofI- and tofR-independent pathways, respectively. Especially, the ORF (bglu_2g06320) divergently transcribed from toxJ, which encodes an orphan LuxR protein and controls toxoflavin biosynthesis, was newly identified in this study as a gene required for the tofR-independent toxoflavin production and named as toxK. Among those genes, flhD, dgcB, and wyzB were further studied to validate their functions in the tofI-independent toxoflavin production, and similar studies were also conducted with qsmR and toxK for their functions in the tofR-independent toxoflavin production. This work provides a foundation for future comprehensive studies of the intercellular signaling systems of B. glumae and other related pathogenic bacteria.